(untitled) (International journal of artificial intelligence, 2026)
This article examines the stages of morphofunctional maturation of the cardiovascular system in children and adolescents aged 7 to 17 years. Particular attention is paid to age-related changes in heart rate, arterial blood pressure, and the mechanisms of autonomic regulation, including the interaction between sympathetic and parasympathetic influences. The relationship between ontogenetic development, academic workload, and the risk of functional cardiovascular deviations such as tachycardia, blood pressure instability, and vegetative-vascular dystonia is analyzed.